Transesterification of jatropha oil using a mixture of natural shells as solid catalyst. Issue 4 (3rd July 2016) - Eswararao, Y.; Niju, S.; Meera Sheriffa Begum, K.M.; Anantharaman, N.; Malik Raj, S.
ABSTRACT: Heterogeneous CaO catalyst was synthesized from renewable sources clam shells (CS) and egg shells (ES). The mixed composition of the CS–ES catalyst was utilized for the preparation of biodiesel via transesterification of jatropha oil. The catalyst was characterized using X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), and Scanning Electron Microscopy (SEM). The conversion of biodiesel was determined by 1 H Nuclear Magnetic Resonance Spectroscopy ( 1 H NMR) and the functional groups in the biodiesel were identified using FTIR spectroscopy. The mixture of catalyst (70% CS and 30% ES) obtained a maximum biodiesel conversion of 97.54% using 7 wt% catalyst (based on oil weight) at methanol to oil molar ratio of 12:1, reaction temperature of 65 °C and reaction time of 3 h.